Impact of Need for Achievement on Entrepreneurial Intentions; Mediating Role of Self-Efficacy - Akhtar, Shamim; Hongyuan, Tian; Iqbal, Shuja; Ankomah, Fred Yaw Nyarko (Journal of Asian Business Strategy, 2020)
Entrepreneurship is becoming very significant for the growth of economies since last decade. Therefore this study aimed to analyze the factors affecting the intentions of individuals towards entrepreneurial start-up so that economic growth can be increased. Entrepreneurial intentions are the vital component of actual business setups that need several personality traits to place ideas into actual actions. Hence the study constructed two personality traits that affect these intentions. The need for achievement and self-efficacy are significant variables to be analyzed in entrepreneurship while discussing the generating of new entrepreneurial businesses. A quantitative analysis was performed using Smart PLS on the collected data from 123 questionnaire responses provided by small and medium-size new entrepreneur start-ups. The findings reveal that the need for achievement and self-efficacy significantly affects the intentions of entrepreneurs (direct effects). Moreover, the study also explained that the need for achievement has a positive and significant impact on entrepreneurial intentions when mediated by self-efficacy behavior (indirect effect). The study provides theoretical concepts of the selected variables along with significant practical implications for entrepreneurial businesses.